HYPOPHOSPHATEMIC RICKETS: CASE REPORT - Maia, Marta Liliane de Almeida (Rev Paul Pediatr, 2018)
OBJECTIVE: Early diagnosis and immediate treatment of hypophosphatemic rickets is of utmost importance as it may prevent subsequent sequelae. This report aims at warning pediatricians to consider the presence of the disease. CASE DESCRIPTION: Description of the metabolic profile, creatinine clearance, nutritional status, weight and body structure of a patient who presented the clinical-laboratorial characteristics of hypophosphatemic rickets and was followed in an outpatient clinic for tubulopathies over the period of 12 months. The patient had been bedridden for some time, was dependent on mechanical ventilation and presented an altered metabolic bone condition. Treatment was phosphate (initial: 65 mg/kg/day and final: 24,2 mg/kg/day), calcium (initial: 127 mg/kg/day, final: 48,4 mg/kg/day) and calcitriol (initial: 0.06 mcg/kg/day, final: 0.03 mcg/kg/day). The patient improved, evolving into spontaneous breathing and walking unaided. Laboratory results: calcium (mg/dL) initial 7.1, final 10.1; phosphate (mg/dL) initial 1.7 final 3.2; magnesium (mg/dL) initial 1.5 final 2.1, parathyroid hormone (pg/l) initial 85.8, final 52.7, alkaline phosphatase (UI/l) initial 12660, final 938; there was also improvement in weight/structural development (Z score: H/A initial: -6.05, final -3.64; W/A: initial -2.92, final -1.57) with presence of transitory gallstones. Creatinine clearance (mL/min/1.73m(2)bsa) was constant. The medication improved his laboratory results and nutritional status, but the patient did not return for two years for follow-up and, during this period, his condition has noticeably deteriorated. COMMENTS: Early diagnosis and follow-up are essential in dealing with this pathology.